226k views
3 votes
I really don't know where to start with this, but you have to solve for x.

(2x-90)+(2x-90)+x=180

User TestTester
by
5.0k points

1 Answer

3 votes

Answer:

x = 72

Explanation:

We first remove the parenthesis

2x-90+2x-90+x = 180

Group like terms

2x+2x+x-90-90 = 180

Add the like terms with each other

5x-180 = 180

Add 180 to both sides to cancel the -180 on the left side of the equation

5x = 180+180 = 360

We then divide 360 by 5 to get 72 as x

User Daniel Brady
by
6.0k points